Response mechanisms to acid stress promote LF82 replication in macrophages - Ting Yao; Ting Yao; Yu Huang; Yu Huang; Zimeng Huai; Zimeng Huai; Xingmei Liu; Xingmei Liu; Xiaowen Liu; Yutao Liu; Yutao Liu; Hao Sun; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
BackgroundAdherent–invasive E. coli (AIEC) LF82 is capable of adhering to and invading intestinal epithelial cells, as well as replicating within macrophages without inducing host cell death.MethodsWe compared the transcriptomics of LF82 at pH=7.5 and pH=5.8 by RNA-sequencing, and qRT-PCR verified differentially expressed genes (DEGs). The deletion mutants of DEGs in the treatment group (pH=5.8) compared to the control group (pH=7.5) were constructed by λ recombinant. The replication differences between the mutants and WT infected Raw 264.7 at 24 h.p.i were analyzed by combining LB solid plate count and confocal observation. NH4Cl and chloroquine diphosphate (CQ) were used for acid neutralization to study the effect of pH on the replication of LF82 in macrophages. Na2NO3 was added to RPMI 1640 to study the effect of nitrate on the replication of LF82 in macrophages. 0.3% solid LB was used for flagellar motility assay and Hela was used to study flagellar gene deletion mutants and WT adhesion and invasion ability.ResultsIn this study, we found that infection with LF82 results in acidification of macrophages. Subsequent experiments demonstrated that an intracellular acidic environment is necessary for LF82 replication. Transcriptome and phenotypic analysis showed that high expression of acid shock genes and acid fitness genes promotes LF82 replication in macrophages. Further, we found that the replication of LF82 in macrophages was increased under nitrate treatment, and nitrogen metabolism genes of LF82 were upregulated in acid treatment. The replication in macrophages of ΔnarK, ΔnarXL, ΔnarP, and Δhmp were decreased. In addition, we found that the expression of flagellar genes was downregulated in acidic pH and after LF82 invading macrophages. Motility assay shows that the movement of LF82 on an acidic semisolid agar plate was limited. Further results showed that ΔfliC and ΔfliD decreased in motility, adhesion ability, and invasion of host cells, but no significant effect on replication in macrophages was observed.ConclusionIn this study, we simulated the acidic environment in macrophages, combined with transcriptome technology, and explained from the genetic level that LF82 promotes replication by activating its acid shock and fitness system, enhancing nitrate utilization, and inhibiting flagellar function.